N'-(2-Hydroxy-5-nitrobenzylidene)-2-(1H-indol-3-yl)acetohydrazide - Puvaneswary, Subramaniam; Ali, Hapipah Mohd; Robinson, Ward T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The molecule of the title compound, C(17)H(14)N(4)O(4), uses its amide-NH-group to form a hydrogen bond to the amido-C(=O)-group of an adjacent molecule to furnish a linear chain structure. The hydroxy group forms an intramolecular hydrogen bond; the indolyl-NH-unit does not engage in any strong hydrogen-bonding interactions.